Penerapan Pembiayaan Murabahah Pada PT BPRS PUDUARTA INSANI - Lenti Susanna Saragi; Danita Febryanti Br Simatupang; Julaidi Selian; Karen Orelia Gulo; Sendiana Br Ginting; Yolanda Tampubolon (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Islamic banking is currently on the rise and has become a community reference, one of which is financing using a profit-sharing system. For this reason, various Islamic banking products must be understood by the public, one of which is the application of murabaha contracts to financing products at PT. PUDUARTA INSANI Sharia People's Financing Bank (BPRS). This article discusses the Application of Murabaha Contracts in Financing Products at PT. PUDUARTA INSANI Sharia People's Financing Bank (BPRS). The results of this study are that the application of the contract used in financing is a murabaha contract, namely the sale and purchase of goods at the original price with an additional agreed profit. In technical terms, Murabahah Islamic banking is defined as an agreement agreed upon between an Islamic bank and a customer, in which the bank provides financing for the purchase of raw materials or other working capital needed by the customer.